Vibration energy harvesting using piezoelectric materials - Tang, Lihua (2012)
Harvesting environmental energy around a system provides a promising solution to implement self-powered electronic devices, which currently rely on batteries as power supply. Vibration energy is a ubiquitous energy source in the environment which can be converted into electricity via different transduction mechanisms. Due to their high power density and ease of application, piezoelectric materials have been enthusiastically pursued for vibration-to-electricity transduction. The work in this thesis focuses on developing advanced modeling methods for piezoelectric energy harvesting systems and improving their efficiency from both sophisticated interface circuit and advanced mechanical configuration perspectives.